Metal-Free Regiodivergent Addition of Carbon Nucleophiles to α,β-Unsaturated Electrophiles - Spitz, Cédric (Molecules, 2017)
A mild and metal-free regiodivergent addition of carbon nucleophiles to α,β-unsaturated electrophiles was developed. Total 1,2-regioselectivity was observed in the addition of nitrobenzyl chloride derivative 1 to α,β-unsaturated aldehydes 2 in the presence of TDAE. Moreover, the reaction between p-nitrobenzyl chloride 1a and α,β-unsaturated iminium salts 4 led to the formation of the 1,4-adduct with total regioselectivity.